2019
DOI: 10.5958/0974-9357.2019.00115.6
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of High Neonatal Mortality Rates in Migori County Referral Hospital in Kenya

Abstract: I declare that DETERMINANTS OF HIGH NEONATAL MORTALITY RATES IN MIGORI COUNTY REFERRAL HOSPITAL IN KENYA is my own work and that all the sources that I have used or quoted have been indicated and acknowledged by means of complete references.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 172 publications
0
2
0
Order By: Relevance
“…[ 35 36 ] This information is mostly gathered through nursing assessment which includes information concerning the patient's individual physiological, psychological, sociological, and spiritual needs. [ 37 ] Appreciation of some of the social factors (non-clinical)[ 38 ] that influence health-related behaviors and health status itself can help nurses develop more effective treatment plans when caring for these vulnerable groups. [ 39 ] The child developmental problems combined with the socioeconomic disadvantage are most responsible for the health inequalities faced by ASD children's families hence the need for nurses advocacy.…”
Section: Discussionmentioning
confidence: 99%
“…[ 35 36 ] This information is mostly gathered through nursing assessment which includes information concerning the patient's individual physiological, psychological, sociological, and spiritual needs. [ 37 ] Appreciation of some of the social factors (non-clinical)[ 38 ] that influence health-related behaviors and health status itself can help nurses develop more effective treatment plans when caring for these vulnerable groups. [ 39 ] The child developmental problems combined with the socioeconomic disadvantage are most responsible for the health inequalities faced by ASD children's families hence the need for nurses advocacy.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the latest study have shown that the neonatal mortality rate for Kenya in 2018 was 19.6 deaths per 1000 live births. The rate of neonatal mortality steadily fell from 35.4 deaths per 1000 live births in 1975 14 . A report published by Africa Institute of Development Policy (AFIDEP) in 2020, shows that neonatal mortality in Wajir was indicated as 24 per 1000 live births in 2017 15 .…”
Section: Problem Statementmentioning
confidence: 99%